Security in computing and communications 7th International Symposium, SSCC 2019, Trivandrum, India, December 18-21, 2019, Revised Selected Papers /: 7th International Symposium, SSCC 2019, Trivandrum, India, December 18-21, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available